Analysis of single-module and cascade molecular analog circuits for approximate computing based on DNA Strand Displacement - Oliveira, Poliana; Fonte Boa, Maria; Marks, Renan; Guterres, Marcos; Vilela Neto, Omar (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
Emerging technologies, as DNA computing, promise to help with early diagnosis and disease treatments. For this purpose, molecular circuits design needs to become easier and feasible. Based on previous works, we built arithmetic analog circuits in single and cascade modules of different sizes using DNA Strand Displacement reactions. This paper aims to analyze such circuits for approximate computing. The simulation results showed that the circuit must be specific since its processing capacity (defined by the input range) reduces accuracy and scalability. In adders, the output error decreases when the inputs are close to the maximum, while in subtractors, a pattern was not observed. Moreover, leak reactions compromise the accuracy, especially for the cascade versions. This conclusion indicates that analog single-modules can be a better design alternative.